Ruang Publik "Fishing Space": Sarana Pertukaran Informasi Bisnis pada Masyarakat Perdesaan Kampung Pasir Kalong - Agus Mauluddin (Brawijaya Journal of Social Science, 2019)
Public space in the meaning of Habermas (2015) is a space created, in which there are discussions of business issues that gradually until the discussion of social issues more broadly. Through the public space, the freedom to gather, speak, argue, and arguments can be created. BD informant revealed that fishing activities in Pasir Kalong village became a space for exchanging business information, socializing media with other residents, and exchanging information regarding the problems of the village.